Kulturarv — ikon för en sekulariserad tid? - Wangefelt Ström, Helena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
This article examines how the term "holiness" can be applied to the discussion about cultural heritage, and raises the question whether cultural heritage might even have substituted institutionalized religion as an object of devotion in a secularized society. A comparison between the religious field and the heritage field is performed by studying two specific examples, the Trinity icon and the medieval wall surrounding Visby. Different aspects of these examples are examined, such as Creating distance — creating intimacy; Pedagogical example — The real thing; Who is the Subject — Who's viewing who?; To bless and to petrify; and Between preservation and use, form and function. The parallels between the religious field and the heritage field makes the author state the necessary comeback of "holiness" as a factor — especially important in a society of an increasing cultural diversity.